2009
DOI: 10.3200/35-08-014
|View full text |Cite
|
Sign up to set email alerts
|

Horsing Around: Spontaneous Four-Legged Coordination

Abstract: Motivated by previous research suggesting that informational and mechanical interlimb coupling can stabilize rhythmic movement patterns, the authors show that stable 4-legged patterns between 2 individuals, either walking or running, can emerge unintentionally from simple forms of coupling. Specifically, they show that the leg movements of pairs of naive individuals become spontaneously phase locked when visually or mechanically coupled via a foam appendage. Analysis of each of the phase locked trials revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…Such monitoring may rely on visual information, but may be driven by haptic information available through physical coupling, as well (see Harrison & Richardson, 2009;. In addition, people may employ signaling (Vesper & Richardson, 2014) and speeding (Vesper, van der Wel, Knoblich, & Sebanz, 2011) as strategies to accomplish joint goals.…”
Section: Discussionmentioning
confidence: 99%
“…Such monitoring may rely on visual information, but may be driven by haptic information available through physical coupling, as well (see Harrison & Richardson, 2009;. In addition, people may employ signaling (Vesper & Richardson, 2014) and speeding (Vesper, van der Wel, Knoblich, & Sebanz, 2011) as strategies to accomplish joint goals.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both and Harrison and Richardson (2009) found that visual information was effective for unintentional gait synchronization, during side-by-side treadmill walking or in an over-ground walker-behind-walker setting, respectively. As described above, treadmill walking differs from over-ground walking because of several factors.…”
Section: What Are the Mechanisms Of Synchronization? The Effects Of Smentioning
confidence: 95%
“…As more attention -especially visual -is paid to the changing sensory environment, the movements of the partner may attract less spontaneous attention, leading to lower coupling and less synchronization. This effect was countered in Harrison and Richardson (2009) by instructing the partners to stay within a fixed distance of 0.75 m, one behind the other. During treadmill walking, visual attention is either free to wander, or may putatively include the section of the belt just in front of the walker's feet, in order to judge the distance from the end of the walking surface.…”
Section: What Are the Mechanisms Of Synchronization? The Effects Of Smentioning
confidence: 97%
“…Bipedal gait analysis required students to estimate the time-averaged gait cycle (with 95% confidence interval) for ankle, knee, and hip and to estimate phaserelations under the different manipulations of walking with eyes open or with eyes closed. Next, we borrowed from a research paradigm that investigated intralimb coordination between dyads linked mechanically together while walking, e.g., with the hands of the rear walker on the shoulders of the front walkers (Harrison & Richardson, 2009). Lastly, I encouraged students to take the motion-capture suits across the campus, to find accessibility problems, and to examine how different constraints (e.g., walking with a crutch or with a heavy backpack) changed the movement coordination situated in its context.…”
Section: The Motion-capture Classmentioning
confidence: 99%